TNF-α inhibitor ameliorates immune-related arthritis and pneumonitis in humanized mice - Gao, Jian; Miao, Jinlin; Sun, Haoyang; Fu, Xianghui; Zhang, Peiyan; Chen, Zhinan; Zhu, Ping (Frontiers in Immunology, 2022)
Objectives This study aimed at establishing a mouse model of immune-related adverse in humanized BALB/c-hPD1/hCTLA4 mice to investigate their potential pathogenesis and explore therapeutic targets for immune-related arthritis and pneumonitis. Methods Humanized BALB/c-hPD1/hCTLA4 mice were injected with vehicle or collagen-specific antibodies (CA) and immune checkpoint inhibitors (ICI, ipilimumab, anti-human CTLA-4; and nivolumab, anti-human PD-1), and some mice were treated with anti-TNF-α antibody, leading to the control, collagen antibody-induced arthritis (CAIA), CAIA+ICI and treatment groups. The severity of clinical arthritis and pneumonitis in mice was monitored longitudinally and the pathological changes in the joints and lungs were histologically analyzed and the contents of lung hydroxyproline were measured. The frequency of different subsets of T cells was analyzed by flow cytometry and multiplex immunofluorescency. Results Compared with the control, the ICI group of mice developed the delayed onset of moderate degrees of arthritis while the CAIA+ICI group of mice exhibited the early onset of severe arthritis. Treatment with ICI caused severe pneumonitis, especially in the mice with CA. Flow cytometry analysis indicated a significantly higher frequency of splenic TNF-α+CD4+ and TNF-α+CD8+ T cells, but not other subsets of T cells tested, in the CAIA+ICI group of mice, relative to that in other groups of mice. Treatment with anti-TNF-α significantly mitigated the severity of arthritis and pneumonitis as well as deposition of collagen in lung of mice. The treatment also decreased the frequency of TNF-α+CD4+ and TNF-α+CD8+ T cells as well as effector memory T cells in the periphery lymph orangs and lungs of mice. Conclusions We successfully established a humanized mouse model of ICI-related severe arthritis and pneumonitis with a higher frequency of TNF-α+ T cells, which were significantly mitigated by anti-TNF-α treatment. Conceptually, ICI treatment can induce multiple autoimmune-like diseases in autoimmune-prone individuals and TNF-α+ T cells may be therapeutic targets for intervention of immune-related arthritis and pneumonitis.